The Impact of Job Characteristics on Private Prison Staff: Why Management Should Care - Hogan, Nancy L. (American journal of criminal justice, 2009)
The number of private prisons run by corporate security businesses has increased rapidly throughout the past two decades. There has been a parallel increase in literature, both pro and con, comparing the efficiency and effectiveness of private and public prisons; however, private prison staff has been largely ignored. OLS regression analysis of a survey of 160 employees at a Midwestern private prison facility showed that the job characteristics of job stress, supervision, and job variety were far more important than personal characteristics of race/ethnicity, gender, age, tenure, education and position in influencing staff job satisfaction and organizational commitment. Specifically, job stress had the largest impact on job satisfaction, while quality of supervision had the greatest impact on organizational commitment.